Aquaporin-3 and aquaporin-4 are sorted differently and separately in the trans-Golgi network. - Eva C Arnspang (PLoS ONE, 2013)
Aquaporin-3 (AQP3) and aquaporin-4 (AQP4) are homologous proteins expressed in the basolateral plasma membrane of kidney collecting duct principal cells, where they mediate the exit pathway for apically reabsorbed water. Although both proteins are localized to the same plasma membrane domain, it is unknown if they are sorted together in the Golgi, or arrive in the same or different vesicles at the plasma membrane. We addressed these questions using high resolution deconvolution imaging, spinning disk and laser scanning confocal microscopy of cells expressing AQP3 and AQP4. AQP3 and AQP4 were observed mostly in separate post-Golgi carriers, and spinning disk microscopy showed that most of AQP3 and AQP4 were delivered to the plasma membrane in separate vesicles. In contrast, VSV-G and LDL-R, two well-characterized basolateral proteins, co-localized to a high degree in the same post-Golgi carriers, indicating that the differential sorting of AQP3 and AQP4 is specific and regulated. Significantly, a chimeric AQP3 containing the AQP4 cytoplasmic tails co-localized with AQP4 in post-Golgi vesicles. These results indicate that AQP3 and AQP4 are separated into different post-Golgi carriers based on different cytoplasmic domain sorting signals, and are then delivered separately to the plasma membrane.